2013
DOI: 10.5070/d3196018558
|View full text |Cite
|
Sign up to set email alerts
|

Diseases associated with hidranitis suppurativa: part 2 of a series on hidradenitis

Abstract: Hidradenitis suppurativa (HS), a pathologic follicular disease, impacts patients' lives profoundly and usually occurs in isolation. The diseases with the strongest association are obesity, depression, and pain. HS is associated with many diseases including acne conglobata (AC), dissecting cellulitis, pilonidal cysts, and obesity. Pyoderma fistulans sinifica (fox den disease) appears to be the same entity as Hurley Stage 2 of 3 HS. The rate of acne vulgaris in HS patients mirrors unaffected controls. The most c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(11 citation statements)
references
References 157 publications
0
10
0
1
Order By: Relevance
“…Musculoskeletal association with HS has been reported 2 . It was shown that there is an association with skin flares and that it tends to occur years after the onset of skin disease.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Musculoskeletal association with HS has been reported 2 . It was shown that there is an association with skin flares and that it tends to occur years after the onset of skin disease.…”
Section: Discussionmentioning
confidence: 97%
“…The disease primarily affects the axillary, perineal, inguinal, intermammary, and inframammary regions 1 . Several autoimmune conditions and rheumatologic disorders have been associated with HS 2 . Herein, we report an unusual case of a patient with HS and relapsing polychondritis (RPC).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature, multiple cases of concurrent HS and PG (syndromic HS) have been described [ 16 , 17 ], with HS commonly preceding PG lesions by several months to years [ 18 ]. Several autoinflammatory arthritic-pyodermic syndromes like PG, acne, and HS (PASH) and PG, acne, pyogenic arthritis, and HS (PAPASH) have been recognized, some of them manifesting systemic symptoms of high fever and joint pain along with increased inflammatory activity in the blood and/or skin such as CRP, ESR, TNF-α, and interleukin-1 [ 19 , 20 , 21 ]. Moreover, a case of overlapping IGM and HS has been reported [ 22 ], in which the authors suggested that IGM might be a localized form of HS and that the link between these two entities may have been missed since IGM and HS patients are seen by gynecologists and dermatologists, respectively [ 22 ].…”
Section: Discussionmentioning
confidence: 99%